Girl Mossing, Rotting, and Resistance: Relational Naturalism and Dying Well Together - Hannah Gould; Anna Halafoff (Religions)
Living and dying well together in the Anthropocene, in the context of intensifying climate crises, global pandemics, and fast-paced hustle culture, is an increasingly daunting task. While many wellness movements call for strict regimes and vigorous activity, striving for largely unattainable bodily norms and longevity, an emerging trend centres on embracing natural processes and temporalities of resistance focused on relaxation, rest, and even decay. So-called ‘girl mossing’ and ‘girl rotting’ encourage women to be intentionally unproductive, and to spend time instead lying on a forest floor, staring up at a canopy of trees, caressing moss. Similarly, members of the ‘death positive’ and ‘new death’ movements advocate for sensorial connection with nature at the end of life, and for an embrace of practices of decay and decomposition. Both trends are dominated by women and influenced by Buddhist and Pagan traditions. They also exemplify spiritual complexity, particularly relating to biomedicine and consumerism. Examining these interconnected lifestyle and deathstyle movements, this article considers the uptake of ‘relational naturalism’ in contemporary societies as an antidote to the personal and planetary harms of neoliberal capitalism.